Adaptive simultaneous pervasive visible light communication and sensing - GOKARN, Ila Nitin (Institutional Knowledge at Singapore Management University, 2021)
Driven by the rapid growth in the proliferation of low-cost LED luminaries, visible light is being increasingly explored as both a high-speed communication and sensing channel for a variety of IoT applications. Visible Light Communication (VLC) exploits the high-frequency modulation of an optical source while ensuring imperceptibility to the human eye. In parallel, recent approaches in Visible Light Sensing (VLS) have demonstrated how high frequency optical strobing can be used to perform vision-based remote sensing of mechanical vibrations (e.g., of factory equipment). To date, exemplars of VLC and VLS have, however, been explored in isolation, without consideration of their mutual dependencies. In this work, we explore future visible light-based pervasive computing scenarios, where strobing and high-frequency signal modulation are used concurrently to support both VLC and VLS. We demonstrate that there is in fact a fundamental tradeoff between the desires for high VLC throughput and wide VLS coverage: such a tradeoff is driven by the duty cycle of the strobing light source, such that a larger duty cycle results in higher communication throughput but reduced sensing resolution, and vice versa. We then discuss two approaches under exploration to overcome this limitation (i) Alternating VLC and VLS mechanisms in a single-LED system (ii) Multi-harmonic adaptive strobing in a multi-LED system.